PENGARUH PENDIDIKAN, UPAH DAN ANGKA HARAPAN HIDUP TERHADAP PRODUKTIVITAS TENAGA KERJA SEKTOR EKONOMI DI PROVINSI - Sudirman Sudirman; Ahmadi Ahmadi (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
Education in an organization is a process towards the development of capabilities desired by the organization concerned . While drills and emergency training is part of a process of education that aim to improve one's ability or special skills to know a group of people . education in general related to preparing candidates required by an agency or organization while exercise / training associated with increased capabilities or skills of employees who have occupied a particular job or task. Produktitivitas measurement is a key indicator of the progress of economic theory as well as to a nation or a specific industry that is closely related to the real incomes of workers' living standards . Productivity is a measure of the ability of the factors of production to produce an output or as a measure of the level of efficiency and the Effectiveness of each resource that is used during the process of ongoing productivity , by comparing the amount of output used .Keyword :  education, productivity, economic sectors